The Association Between Publication Record and Career Path for Facial Plastic and Reconstructive Surgery Fellowship Applicants - Khodayar Goshtasbi; Amir A. Hakimi; Daniel Kim; Brian J. F. Wong (Laryngoscope Investigative Otolaryngology)
ABSTRACT Introduction It is unknown whether the publication productivity of facial plastic and reconstructive surgery (FPRS) fellowship applicants before fellowship can be a predictor of pursuing academics in the future. The objective of this study was to assess whether the publication productivity of a cohort of FPRS fellowship applicants was associated with their eventual career path of academic versus non‐academic practice. Methods This was a retrospective analysis of a cohort of FPRS fellowship applicants who applied to a single institution from 2012 to 2016. Their submitted publication records at the time of the application process, and their current career positions were queried. Results Thirty‐four (27%) of the 125 fellowship applicants are currently in academic positions with no difference in genders (p = 0.66). Academic FPRS clinicians had a significantly higher number of total publications (6.3 ± 5.1 vs. 4.4 ± 3.9, p = 0.03), first author publications (3.4 ± 3.2 vs. 2.1 ± 2.5, p = 0.01), and publications in otolaryngology or plastic/aesthetic surgery journals (4.5 ± 3.9 vs. 3.1 ± 3.3, p = 0.03). There was no difference in the number of plastics, aesthetic, or trauma‐specific publications (p = 0.44). Conclusion The number of publications and publications in otolaryngology or plastic/aesthetic surgery journals, but not necessarily articles with specific plastic/aesthetic/trauma topics, may be a predictor of pursuing academia for FPRS fellowship applicants. Level of Evidence 4.